The relationship between contact force and clinical outcome during radiofrequency catheter ablation of atrial fibrillation in the TOCCATA study - Reddy, Vivek Y.; Shah, Dipen; Kautzner, Josef; Schmidt, Boris; Saoudi, Nadir; Herrera, Claudia; Jaïs, Pierre; Hindricks, Gerhard; Peichl, Petr; Yulzari, Aude; Lambert, Hendrik; Neuzil, Petr; et al. (Heart rhythm, 2012)
The clinical efficacy of catheter ablation of paroxysmal atrial fibrillation (AF) remains limited by difficulty in achieving durable pulmonary vein isolation (PVI). Suboptimal catheter tip-to-tissue contact force (CF) during lesion delivery is believed to reduce clinical efficacy. To determine the relationship between catheter CF during irrigated catheter ablation for AF and clinical recurrences during follow-up. Thirty-two patients with paroxysmal AF underwent PVI by using a radiofrequency ablation catheter with a CF sensor integrated at its tip, and they were followed for 12 months. The relationship between the CF and clinical outcomes was determined. Acute PVI was achieved in 100% of the veins. Thirty-five percent (351 of 1017) of the applications were placed with an average CF of <10 g (low CF). All patients treated with an average CF of <10 g (5 of 5 patients) experienced recurrences, whereas 80% of the patients treated with an average CF of >20 g (8 of 10 patients) were free from AF recurrence at 12 months. The analysis of the average force-time integral showed that 75% of the patients treated with <500 gs were recurrent whereas only 31% of the patients treated with >1000 gs had recurrences at 12 months. The CF during catheter ablation for AF correlates with clinical outcome. Arrhythmia control is best achieved when ablation lesions are placed with an average CF of >20 g, and clinical failure is universally noted with an average CF of <10 g.